The perceptions of morality of secondary school learners: a cross-cultural study - J. Coetzee; D. A. Louw; J. C. Jooste (Acta Theologica)
The focus of this research is to determine the perceptions of morality among a group of young South Africans. More specifically, the possible role that gender, culture, lifestyle, religion and sexual practices in these perceptions of morality may play will be investigated. To date, no studies have attempted to measure the youth’s perceptions of morality. Consequently, little South African literature is available. While many variables are believed to influence the development and expression of morality, the variables that were measured in this study included gender, culture, lifestyle, sexual experience and religion, as found in literature. Seven schools were involved in this study. They were classified as being high, average and below average with regards to academic performance. After statistical analysis, the variable found to have the greatest influence on the perception of morality was gender. A core finding of this study was that the female learner’s responses point towards a higher level of morality than the male learners do. This study also found cultural differences with regard to morality. Frequency of religious practices was also found to have an influence on moral expression. The study also indicated that past sexual experience has an effect on the perception and expression of morality. Lifestyle was not found to be a significant factor in the perception of morality in this study. The results of the research will help to give clearer understanding of the youth’s perception of morality, which could then be incorporated into combating immorality, for example, through developing programmes in this regard. For future and especially comparative purposes, the findings of this study could also serve as a base-line measurement of the perceptions of morality among the South African youth, should one wish to determine to what extent these perceptions are static or dynamic.